Gentamicin Upregulates the Gene Expression of hla and nuc in Staphylococcus aureus - Alkhafajy, Rand Thair Abdulateef; Al-Mathkhury, Harith Jabbar Fahad (Iraqi Journal of Science, 2023)
The current study aimed to detect the effect of gentamicin stress on the expression of hla (encodes hemolysin) and nuc (encodes nuclease) genes of Staphylococcus aureus. Fifty-eight isolates identified as S. aureus were isolated locally from different clinical specimens. Disk diffusion method was used to detect the resistance to S. aureus. The minimum inhibitory concentration (MIC) of gentamicin was estimated by broth microdilution method. hla and nuc genes were determined by polymerase chain reaction technique. The biofilm was evaluated using the microtiter plate method in the presence and absence of gentamicin at sub-MIC. The results showed that 18 (31%) and 40 (69%) S. aureus isolates were sensitive and resistant to gentamicin, respectively. All S. aureus isolates succeeded in forming biofilm. However, eight (13.79%), 28 (48.28%) and 22 (37.93%) isolates produced weak, moderate and strong biofilms respectively. In most isolates, gentamicin at sub-MIC decreased biofilm intensity. Due to gentamicin stress, the hla and nuc genes were upregulated in S. aureus biofilm.